Design and construction of a website to encourage the adoption of reading habits in early childhood: systematization of an experience - Sánchez Madrigal, Pilar (2024)
Linking reading with the boy or girl from birth is a fundamental aspect for their comprehensive development, since, although the infant has not learned to interpret the alphabetic signs, they will begin to have stimuli that will generate an approach to books. and you could gradually acquire important skills that will help you in your comprehensive development. In Costa Rica, efforts have been made to strengthen the habits of readers in early childhood, developing programs from different entities, however, in the latest Reports on the State of Education, the shortcomings in reading of those who are part of the Costa Rican Educational System continue to be highlighted. . Designing a website using the Design Thinking methodology so that family managers, caregivers, teachers and librarians can encourage the adoption of reading habits in boys and girls in the early childhood stage, can correct the reading deficiencies detected, since Through this tool, a taste for reading could be developed not only in the early childhood population but also in the people in charge of their care. This project was approached through a research action that is framed within a qualitative approach, in which they participated as coordinators or heads of educational libraries as well as preschool experts and information professionals who work with the early childhood population. With the information obtained and investigated and following the five design stages of Design Thinking, a website divided into three sections was structured and it was concluded that although it is true, there are multiple resources and educational activities in the digital world, not all of them can be used or published due to its copyright restrictions; likewise, some digital resources are not designed to generate the required impact on the study population.